Improved biomass and protein production in solid-state cultures of an Aspergillus sojae strain harboring the Vitreoscilla hemoglobin - Mora Lugo, Rodrigo (2015)
The biotechnological value of Aspergillus sojae ATCC 20235 (A. sojae) for production of pectinases in solidstate fermentation (SSF) has been demonstrated recently. However, a common drawback of fungal solid-state cultures is the poor diffusion of oxygen into the fungi that limits its growth and biological productivity. The bacterial Vitreoscilla hemoglobin (VHb) has favored the metabolism and productivities of various bacterial and yeast strains besides alleviating hypoxic conditions of its native host, but the use of VHb in filamentous fungi still remains poor explored. Based on the known effects of VHb, this study assessed its applicability to improve A. sojae performance in SSF. The VHb gene (vgb) under control of the constitutive Aspergillus nidulants gpdA promoter was introduced into the genome of A. sojae by Agrobacterium-mediated transformation. Successful fungal transformants were identified by fluorescence microscopy and polymerase chain reaction (PCR) analyses. In solid-state cultures, the content of protease, exopolygalacturonase (exo-PG), and exo-polymethylgalacturonase (exo-PMG) of the transformed fungus (A. sojae vgb+) improved were 26, 60, and 44 % higher, respectively, in comparison to its parental strain (A. sojae wt). Similarly, biomass content was also 1.3 times higher in the transformant strain. No significant difference was observed in endo-polygalacturonase (endo-PG) content between both fungal strains, suggesting dissimilar effects of VHb towards different enzymatic productions. Overall, our results show that biomass, protease, and exo-pectinase content of A. sojae in SSF can be improved by transformation with VHb.